South Asian farmers avoid losses and earn relatively more income by planting heat- and drought tolerant hybrids based on CGIAR germplasm. - CGIAR Research Program on Maize (2019)
The Heat Tolerant Maize for Asia (HTMA) project helps smallholder farmers in 3 South Asian countries maintain a source of food, feed and income, by developing heat tolerant maize hybrids and getting them out to farmers via licensing to small and medium-size seed companies – the first hybrids got released in the 3rd year of this project!